Open-Book Assessment: A Handbook for Academics - Rooney, Pauline; Johnston, Jonny (Trinity College Dublin, 2021)
This handbook provides an introduction to open-book assessments and contextualises guiding principles for their design, development and implementation in a Trinity context. For many colleagues, open-book approaches to assessment may be unfamiliar territory. This handbook aims to support all staff with teaching responsibilities to find out more about the merits of open-book assessment approaches and it outlines key issues to consider when designing effective open-book assessments.
Keywords: assessment; open-book assessment; academic practice; assessment as learning; assessment for learning; assessment of learning; digital assessment; hybrid learning; online learning; blended learning; Creative Technologies; Digital Engagement; ASSESSMENT; ASSESSMENT AND EXAMINATIONS; Assessment for learning; Assessment of Student Learning; Educational assessment of Students; Online Assessment; Technology and Assessment; academic integrity; constructive alignment; digital assessment; open-book assessment; Education